Instruments for export policy and administration : lessons from the East Asian experience - Rhee, Yung Whee (Washington, D.C. : World Bank, 1985)
The discussions presented in this paper centers around two key concepts: "neutral status" and "extended neutral status." The paper also discusses unconventional policy instruments for export development and stresses the critical contributions of effective institutional mechanisms to the export successes in the East Asian countries.
Summary also in French and Spanish.
Includes bibliographical references: p. 253-267.
osc 18/07/2018
Loans
Keywords: Foreign trade promotion; East, Asia